Association of flavonoid-rich foods and flavonoids with risk of all-cause mortality. Issue 10 (13th June 2017) - Ivey, Kerry L.; Jensen, Majken K.; Hodgson, Jonathan M.; Eliassen, A. Heather; Cassidy, Aedín; Rimm, Eric B.
Abstract: Flavonoids are bioactive compounds found in foods such as tea, red wine, fruits and vegetables. Higher intakes of specific flavonoids, and flavonoid-rich foods, have been linked to reduced mortality from specific vascular diseases and cancers. However, the importance of flavonoid-rich foods, and flavonoids, in preventing all-cause mortality remains uncertain. As such, we examined the association of intake of flavonoid-rich foods and flavonoids with subsequent mortality among 93 145 young and middle-aged women in the Nurses' Health Study II. During 1 838 946 person-years of follow-up, 1808 participants died. When compared with non-consumers, frequent consumers of red wine, tea, peppers, blueberries and strawberries were at reduced risk of all-cause mortality ( P <0·05), with the strongest associations observed for red wine and tea; multivariable-adjusted hazard ratios 0·60 (95 % CI 0·49, 0·74) and 0·73 (95 % CI 0·65, 0·83), respectively. Conversely, frequent grapefruit consumers were at increased risk of all-cause mortality, compared with their non-grapefruit consuming counterparts ( P <0·05). When compared with those in the lowest consumption quintile, participants in the highest quintile of total-flavonoid intake were at reduced risk of all-cause mortality in the age-adjusted model; 0·81 (95 % CI 0·71, 0·93). However, this association was attenuated following multivariable adjustment; 0·92 (95 % CI 0·80, 1·06). Similar results were observed for consumption of flavan-3-ols, proanthocyanidins and anthocyanins. Flavonols, flavanones and flavones were not associated with all-cause mortality in any model. Despite null associations at the compound level and select foods, higher consumption of red wine, tea, peppers, blueberries and strawberries, was associated with reduced risk of total and cause-specific mortality. These findings support the rationale for making food-based dietary recommendations.